Student Activism and the Pandemic: A Global Round-Up - Luescher, Thierry; Türkoğlu, Didem (International Higher Education, 2022)
The COVID-19 pandemic led to far-reaching changes in higher education globally, yet student activism continued to be a force to be reckoned with. Key concerns and commitments remained student funding; equality, social justice, and antidiscrimination; political freedoms and democracy; and gender equality. The single biggest cause of protests was, however, the pandemic itself. Recent additions to the protest agenda include climate change, academic freedom, and the Russian invasion of Ukraine.